Synthesis, Characterization, Biological and Electrochemical Applications of Cerium oxide, Iron oxide and its Mixed Metal Oxide Nanoparticles - Gomuraj Santhanaraj,; Mathavan Alagarsamy,; C. Vedhi, (The Bioscan, 2025)
Energy savings and environmental protection depend critically on the detection and monitoring of exhaust and harmful gases. Metal oxide gas sensors are becoming a more popular option because of their high sensitivity and selectivity, which is driving up demand for low-cost, low-power gas sensors. This research work aims to synthesize and characterize metal oxides, specifically cerium oxide, iron(III) oxide, and CFMMO (Ce-Fe), which is a mixed metal oxide consisting of cerium and iron. The synthesis of nanoparticles is accomplished using the co-precipitation method with a microwave reaction system. The resulting nanoparticles are subsequently characterized utilizing various analytical techniques such as FT-IR, UV-VIS (DRS), FE-SEM, EDAX, AFM, and XRD analysis. The XRD pattern confirmed the cubic fluorite structure of CeO2. In order to investigate the utilization of cerium oxide, iron(III) oxide and cerium iron mixed metal oxides (CFMMO) are used to recognizes of ammonia and hydrogen sulfide with the help of electrochemical method. The binding behavior of metal oxides and ovalbumin were investigated using UV-visible adsorption and fluorescence spectral techniques. The binding constant (Kb), Stern-Volmer constant (Ksv), and fluorophore quenching rate constant (kq) were calculated with the help of spectral data. Using the disc diffusion technique, research has been carried out to investigate the exceptional antibacterial activities of prepared metal oxides and mixed metal oxides against the different bacterial strains.